An integrated model of production and inventory cycles of new and reusable bottling packages in a closed supply chain. Issue 2 (2018) - ,; Rahman, Taufiq; Zhang, David Z.
This paper proposes a model and solution for integrated production and inventory of new and reusable bottling packages. The inventory which did not match the production needs is caused by the difference of production policy and the reverse logistics policy from distribution centre. In addition, this problem is also influenced by cleanliness level of the bottles and the reject bottles during transportation. The solution procedures of this model use algorithm method and simultaneous approach (using software LINGO 14.0). From the calculation, this model obtains a valid result. The company can reduce the inventory cost about 8.88% using enumeration approach and 8.84% using simultaneous approach. Also, this model is not sensitive in terms of changes of parameter to optimum solution.